Developing Self-Confidence in EFL Beginner Learners through Effective Error Correction : a Case Study of the Secondary Schools in Littoral, Benin. - EGOUNLETI, Pédro Marius (My University, 2020)
This research work aims at highlighting the inadequacies associated with the teaching of the English language in Beninese secondary schools. In order to find out some approaches of solutions likely to help teachers better correct students' errors and mistakes during English speaking activities in EFL classes, so as to develop confidence in them, this research uses a methodology focused on a questionnaire addressed to 30 teachers, 5 class visits and interviews with 10 teachers. The data collected show that an increasing number of Beninese EFL teachers ignore the appropriate methods for correcting students' errors during speaking activities and fail in motivating their learners to speak English effectively. As an attempt to redress this situation related to English teaching and learning processes in our secondary schools, the research suggests the organization of adequate training for secondary school teachers who must complete at least a bachelor's degree before being recruited as EFL teachers. In the same perspective, teaching inspectors must intensify their class visits so as to make the EFL teachers aware of their roles as informants, motivators and correctors.
Keywords: developing; self-confidence; errors correction; EFL beginner learners; speaking activities